Ascertainment of vaccination status by self‐report versus source documentation: Impact on measuring COVID‐19 vaccine effectiveness. Issue 6 (11th July 2022) - Stephenson, Meagan; Olson, Samantha M.; Self, Wesley H.; Ginde, Adit A.; Mohr, Nicholas M.; Gaglani, Manjusha; Shapiro, Nathan I.; Gibbs, Kevin W.; Hager, David N.; Prekker, Matthew E.; Gong, Michelle N.; Steingrub, Jay S.; et al.
Abstract: Background: During the COVID‐19 pandemic, self‐reported COVID‐19 vaccination might facilitate rapid evaluations of vaccine effectiveness (VE) when source documentation (e.g., immunization information systems [IIS]) is not readily available. We evaluated the concordance of COVID‐19 vaccination status ascertained by self‐report versus source documentation and its impact on VE estimates. Methods: Hospitalized adults (≥18 years) admitted to 18 U.S. medical centers March–June 2021 were enrolled, including COVID‐19 cases and SARS‐CoV‐2 negative controls. Patients were interviewed about COVID‐19 vaccination. Abstractors simultaneously searched IIS, medical records, and other sources for vaccination information. To compare vaccination status by self‐report and documentation, we estimated percent agreement and unweighted kappa with 95% confidence intervals (CIs). We then calculated VE in preventing COVID‐19 hospitalization of full vaccination (2 doses of mRNA product ≥14 days prior to illness onset) independently using data from self‐report or source documentation. Results: Of 2520 patients, 594 (24%) did not have self‐reported vaccination information to assign vaccination group; these patients tended to be more severely ill. Among 1924 patients with both self‐report and source documentation information, 95.0% (95% CI: 93.9–95.9%) agreement was observed, with a kappa of 0.9127 (95% CI: 0.9109–0.9145). VE was 86% (95% CI: 81–90%) by self‐report data only and 85% (95% CI: 81‐89%) by source documentation data only. Conclusions: Approximately one‐quarter of hospitalized patients could not provide self‐report COVID‐19 vaccination status. Among patients with self‐report information, there was high concordance with source documented status. Self‐report may be a reasonable source of COVID‐19 vaccination information for timely VE assessment for public health action.